REMEDIASI MISKONSEPSI PESERTA DIDIK MENGGUNAKAN MODEL SSCS TENTANG GETARAN DI SMP - Nurul Susilawati; Edy Tandililing; Hamdani Hamdani (Universitas Tanjungpura, 2019)
AbstractThe purposed of this research was to determine the effectiveness of remediation misconception by using Search, Solve, Create, and Share (SSCS) model to reduce the number of the students who have misconceptions about vibration at SMP Negeri 5 Sambas. This research method was pre-experimental with one group pretest-posttest design. This research used intact group random sampling which involved 24 students of VIII C class. The diagnostic test which consists of 12 multiple choices with open reason used to identification students’ misconceptions. Based on data analysis, there was a decrease percentage the number of the students’ who have misconceptions with an average of 75.75 %. The results of the McNemar test showed χ2score (125.83) higher than χ2table (3.84) which means that the students’ conceptual changed significantly after the remediation activity using SSCS model. The remediation effectiveness based on DQM score with an average of 77% (high category). The SSCS model is expected to be used as alternative remediation activities to reduce the number of the students’ who have misconceptions. Keywords: Misconception, Remediation, SSCS, Vibration